The Importance of Realizing Human Capital Based on National and Human Values - Tulkin, Kuyliyev; Xaydarovich, Xudaynazarov Tohtemir (Research Parks Publishers, 2023)
The article analyzes that all the reforms carried out as part of the development strategy in the new Uzbekistan are aimed at developing human capital. In accordance with the development strategy, digitalization processes are widely implemented in our country. Digitalization processes are taking place in all spheres of society. The article also explains that human capital can benefit not only one person, but also others. This is justified by the need to implement it on the basis of national and universal values.